Clot retraction. - Tucker, K; Sage, T; Gibbins, J (2012)
The study of clot retraction in vitro has been adopted as a simple and reproducible approach to assess platelet function. Plasma clots should retract away from the sides of a glass tube within a few hours allowing the rapid characterization of outside-in signaling through platelet integrin α(IIb)β(3). In this chapter, we describe the role of platelets in fibrin clot retraction and provide a detailed description of the methods used to assess this process.